Inverted Takotsubo Syndrome With HELLP Syndrome: A Case Report - Gabarre, Paul; Ruiz, Pablo; Chenevier-Gobeaux, Camille; Charpentier, Etienne; Soulat-Dufour, Laurie; Cohen, Ariel; Monnier-Cholley, Laurence; Chemali, Lotfi; François, Hélène; Kerneis, Mathieu; Lefèvre, Guillaume; Boissan, Mathieu (Frontiers in Cardiovascular Medicine, 2022)
Background: Takotsubo syndrome is a non-ischemic cardiomyopathy involving sudden, transient apical ballooning of the heart muscle that may be triggered by emotional stress and some non-cardiac conditions. Its diagnosis is based on clinical presentation, electrocardiogram, imaging and biomarkers. Case summary: Here, we present a novel case report of a patient presenting very soon after childbirth with an unusual form of Takotsubo cardiomyopathy accompanied by HELLP syndrome. Whereas the overall kinetics of changes in troponin I, troponin T and NT-proBNP levels were similar, the amount of troponin I was much greater and its rate of increase was much faster than that of troponin T. NT-proBNP levels peaked at the same time as the troponins. Discussion: Our findings indicate that assaying circulating cardiac markers, especially troponin I and NT-proBNP, may be most useful for diagnosis of Takotsubo cardiomyopathy. They illustrate the importance of biomarkers in the diagnosis of this disease.